2016
DOI: 10.1002/rmv.1887
|View full text |Cite
|
Sign up to set email alerts
|

Is sunspot activity a factor in influenza pandemics?

Abstract: Extremes of sunspot activity to within plus or minus 1 year may precipitate influenza pandemics. Mechanisms of epidemic initiation and early spread are discussed including primary causation by externally derived viral variants (from space via cometary dust). Efforts to construct a comprehensive early warning system for potential influenza and other viral pandemics that include analysis of sunspot activity and stratospheric sampling for viral variants should be supported. Copyright © 2016 John Wiley & Sons, Ltd. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…The result of linear correlation analysis indicated that the coefficient of correlation between relative sunspot number and cosmic ray data was −0.90 (P=0.000) [9]. Potential influenza pandemics and severe Ebola outbreaks being confined to particular years, we infer that some special or unusual factors must have emerged and played decisive roles.…”
Section: Possible Mechanisms Associated With Sunspots Affecting Influmentioning
confidence: 84%
See 3 more Smart Citations
“…The result of linear correlation analysis indicated that the coefficient of correlation between relative sunspot number and cosmic ray data was −0.90 (P=0.000) [9]. Potential influenza pandemics and severe Ebola outbreaks being confined to particular years, we infer that some special or unusual factors must have emerged and played decisive roles.…”
Section: Possible Mechanisms Associated With Sunspots Affecting Influmentioning
confidence: 84%
“…We now summarise influenza data that have already been discussed at length by Qu [9] elsewhere, and we refer the reader to this work for further details and citations. In the past half century, sporadic cases of severe influenza and deaths in humans have been caused by a number of animal influenza A viruses, including the Hsw1N1virus, first detected in 1976, the H5N1 virus, first detected in 1997, and the H7N9 virus, first reported in 2013.…”
Section: Association Between Influenza and Sunspot Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Hoyle and Wickramasinghe [2][3][4] re-examined this proposal using a more extended dataset and concluded that although the coincidences were not precise, the two sets of data-influenza and sunspot-were phase-locked such that a causal link was likely. This work was recently extended by Qu [5] who found a more generalised result, namely that both certain and possible pandemics fall within ±2 years of sunspot extrema (maxima and minima).…”
Section: Introductionmentioning
confidence: 83%